Evaluating the effectiveness of the abstract transaction model in testing Web services transactions. (30th May 2012) - Casado, Rubén; Tuya, Javier; Younas, Muhammad; Hussain, Farookh Khadeer; Wyrzykowski, Roman; Tudruj, Marek
Summary Web services transactions are used to build efficient and reliable Web applications that are distributed across the Internet and are accessed by multiple simultaneous users. Current research develops various models and protocols to improve the performance and reliability of Web services transactions. However, there is little research on testing the different models and protocols of Web services transactions. This paper presents an abstract transaction model that patterns different Web services transactions standards. This model is capable of deriving concrete models to automatically generate test cases for different Web services transactions standards. The proposed model is implemented as a prototype system and is evaluated using a case of the Jboss Transaction. The evaluation shows that the proposed system has the capability to automatically generate test cases and detect possible failures of transactions running under different Web services transactions standards. Copyright © 2012 John Wiley & Sons, Ltd.